PROBIOTIC AND β-LACTAM SENSITIVITY ASSESSMENT OF LACTIC ACID BACTERIA ISOLATED FROM TRADITIONALLY FERMENTED PRODUCTS OF MEGHALAYA - GHOSH, RAKESH; RAI, AAWAJ KULOONG; JOSHI, S. R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: The present study aimed to isolate, identify, and analyze the probiotic properties and β-lactam sensitivity in the Lactic Acid Bacteria (LAB) prevalent in Tungtap and Lung-seij, common traditionally fermented ethnic products throughout Meghalaya. Methods: Bacterial pure colonies were identified using conventional biochemical tests and 16S rRNA Sanger sequencing. Slightly modified standard protocols were followed for the assessment of different probiotic properties. Results: The selected LAB isolates were found Gram-positive, catalase, and oxidase-negative and exhibited resistance to most of the β-lactam antibiotics used in this study. No significant antibacterial activity was shown against tested strains. However, they showed strong bile salt and acid tolerance, as well as high auto aggregation and moderate hydrophobicity properties, which represent their probiotics properties. Extracellular Polymeric Substances (EPS) yield was highest for the TT2 isolate, while TT10 showed maximal siderophore production. Biofilm formation varied, with BS2 and BS5 showing strong adherence. Sequencing results confirm that the majority of the isolates belonged to the Lactiplantibacillus and Ligilactibacillus genera. Moreover, further genetic analysis confirmed the presence of β-lactamase genes in the selected isolates. Conclusion: The presence of these genes suggests that the isolates may become reservoirs for Antimicrobial Resistance Genes (ARG) in traditional fermented foods. Further study is required to establish whether the isolates are transmitting their antimicrobial resistance genes during co-culture under different stress conditions and transportation.